Characteristics and Destinations of Indigenous Chickens Marketed in Guera Region, East-Central Chad - Youssouf, Mopate Logtene; Nadjissara, Ndjimtoloum; Gueye, El Hadji Fallou (International Journal of Poultry Science, 2011)
The objective of the study was to assess zooeconomic parameters like age, weight, price and destinations of produced chickens that are sold on three main markets of Guera, east-central Chad. Data were collected over six months on the market places of Mongo and Mangalme and four months on the market place of Bitkine. The transversal and retrospective survey was coupled with direct observations and weightings. For 1549 marketed chickens, the males made up 57% and the females 43%. The average values per chicken were found to be 16.2±9.9 months for age, 1082.4±371.2 g for weight and 1607.8±FCFA 414.6 for price. Average age and weight of sold chickens were significantly higher (p<0.001) on Mangalme market, with an average price significantly lower (p<0.001). On the whole, 52% of surveyed chickens were intended for sale in the capital N’Djamena, 39% in Mongo city, 7% in Bitkine and 2% in Mangalme. According to the final destinations declared by buyers, average age and weight of the sold chickens to be consumed in Bitkine were significantly lower (p<0.001) but with an average price significantly higher (p<0.001). The Mangalme sellers sold mainly old chickens in order to earn more money. The pressure exerted by N’Djamena traders to purchase chickens in Bitkine increases prices.